Fabrication of 3D structures via direct ink writing of kaolin/graphene oxide composite suspensions at ambient temperature. Issue 15 (15th October 2019) - Sun, Qinglei; Liu, Jinglong; Cheng, Hao; Mou, Yun; Liu, Jiaxin; Peng, Yang; Chen, Mingxiang
Abstract: Kaolin/graphene oxide composite has been widely utilized in aero-space and architectural engineering applications due to its excellent mechanical property. Direct ink writing (DIW) is a freeform rapid prototyping technology that could be used to accurately fabricate the resulting size with complex shapes. In this study, we reported the DIW of kaolin/graphene oxide (GO) composite suspensions (KGCS) to assemble 3D structures at ambient temperature for the first time. The effects of GO on the chemical constitution and microstructure of kaolin suspensions were investigated. Rheology was characterized to ensure printability of KGCS. The addition of GO in kaolin suspensions quickened a flocculation structure, which dramatically changed their rheology properties. The DIW of 3D structures from the optimal KGCS sample maintained their initial shape without spreading. The flexural and compressive strengths of the dried optimal KGCS samples were obviously enhanced due to the improvement and reduction of the micro-defects compared from cured kaolin matrix.